THE EFFECT OF CLASSICAL MUSIC MOZART THERAPY ON CHANGE THE PAIN SCALE IN POST PATIENTS APPENDICITIS OPERATIONS IN THE DAHLIA ROOM RSUD BOGOR: PENGARUH TERAPI MUSIK KLASIK MOZART TERHADAP PERUBAHAN SKALA NYERI PADA PASIEN POST OPERASI APPENDICITIS DI RUANG DAHLIA RSUD KOTA BOGOR - Dian Dian Novita (Jurnal Ilmiah Wijaya, 2019)
Background : In 2013 based on the WHO (Word Health Organization) records the incidence of appendicitis it was quite high in the world. The issues that occur mortality of appendicitis is 21.000 people, for female population is more high than men. Furthermore, accordings to the records measuremants of Kementrian Kesehatan Republik Indonesia in 2012 is 596.132 people and in 2013 increased to 621.435 people. In Indonesia the incidence of appendicitis infest the highest rank between the other emergency abdomen cases from the result survey of Household Health Survey or SKRT. The profile of Kesehatan Kabupaten/Kota West Java Province in 2015 was gived statement about the pattern of appendicitis at the age group ranges 5 ± 44 years old for hospitalized patients was 24,2%.Research Objective : The purpose in this research is to find out the effect of Mozart’s classical music therapy towards the changes of pain scale in postoperative appendicitis patients in Dahlia Room Bogor Hospital.Research Methods : The type of this research is an experiment with quasi-experimental design and Non Equivalent Control Group design. The population in this studies are all of the post operative appendicitis patients in Dahlia Room Bogor Hospital, with 26 samples researched that using saturated sampling techniques, and the retrievel to complete the material informations were used interview techniques at the preliminary studied and observation sheet when the research was begin. Results of the study :There is shown the differences result of the pain scale before and after intervention group as 0,005, and the differences in the results of the pain scale before and after the control group as 1,000, and the effect of classic mozart’s music therapy towards the changes of pain scale for post operative appendicitis in Dahlia Room Bogor Hospital as 0,007 (p < 0,05). Conclusion : There is a effect of Mozart's classic music therapy toward the changes of pain scale for postoperative appendicitis patients in Dahlia Room Bogor Hospital. The results of this researchmight become knowledge for post operative patients to reduce pain scale by combining medical and non-treatment medical.